Conocimientos y prácticas sobre manejo y prevención de enfermedad diarreica aguda, en madres de ninos/as del Centro Infantil del Buen Vivir Niño Jesús MIES, Loja 2014 - 2015 - Granda Chávez, Daniel Antonio (2015)
The (high-pitched diarrheal disease) HDD is the second cause of infant mortality worldwide, causing the death of 760 billion children in the year 2013 "(1), the present investigation aims to determine knowledge and maternal practices on prevention and management of illness diarrheal in children attending the Center children of the good living Niño Jesus MIES the city of Loja, the research is descriptive, the universe was comprised of 70 mothers, the survey was used to collect the information and as an instrument of the questionnaire, which indicate that mothers most correctly define the concept of HDD; 69% and 66% of them do not know the risk factors, and measures to reduce the risk of producing diarrhea, in terms of knowledge management, more than half of the mothers know the preparation of homemade oral serum and oral rehydration salts as well as signals of signs to prevent complications; However the other half of the study population, does not identify the symptoms or signs to bring it urgently to the health service. Within preventive practices, it was determined that nine exposed indicators, seven of them are carried out properly; Unlike the remaining are the presence of intradomiciliarios animals and care of food prior to intake, which are not practiced properly; and, in terms of the EDA management practices, it was found that this is appropriate. Key words: High-pitched diarrheal disease Knowledge, practices, prevention.